Pemanfaatan Alih Teknologi Industri Otomotif Mengenai Elektrifikasi Hybrid Electric Vehicle (HEV) di Indonesia PT. Toyota Motor Manufacturing Indonesia - Kayla Al Atta (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
This research discusses the utilization of technology transfer in the automotive industry regarding the development of electrified vehicles, with a particular focus on Hybrid Electric Vehicles (HEVs) in Indonesia through the case of PT. Toyota Motor Manufacturing Indonesia. Using a case study approach, the research examines how technology transfer from technologically advanced countries, particularly Japan, has been adopted and adapted to support the development of HEV technology that meets the characteristics and demands of the Indonesian market. The study further analyzes the influence of government policies, regulatory frameworks, industrial collaboration, infrastructure readiness, and consumer preferences on the effectiveness of technology transfer and the implementation of electrified vehicle technology. This research employs a normative juridical method supported by field data obtained through relevant stakeholders and industry observations to provide a comprehensive understanding of the existing conditions. The findings are expected to identify the major challenges and opportunities associated with HEV development and technology localization in Indonesia. Furthermore, this research is intended to provide valuable insights and practical recommendations for automotive industry stakeholders and policymakers in formulating sustainable strategies and regulations that accelerate the development, adoption, and competitiveness of electrified vehicles in Indonesia.